Use of Ambon Banana Skin (Musa Paradisiaca) as a Raw Material for Manufacturing Egg Roll - Daria Sabrina Dorti; Wahyu Mushollaeni; Atina Rahmawati (Indonesian Journal of Food Technology, 2023)
Egg Roll is a type of snack that is baked and then rolled using tongs or a Teflon egg roll mold. and the characteristic of the egg roll itself is that it is a straight roll, tastes sweet, savory and has a crunchy texture. Ambon banana peel is one of the banana wastes that has not been widely used. Even though freshly thrown away Ambon banana peels have no economic value, they are protein, calcium, phosphorus, iron, and contain vitamins B6 and B12. Therefore, in this study, researchers used Ambon banana peels as raw material for making egg rolls. The aim of this research is to obtain the correct formulation for adding Ambon banana peel (Musa Paradisica) to produce egg rolls with the best organoleptic quality and to find out the business feasibility analysis of egg rolls with the addition of Ambon banana peel (Musa Paradisiaca) resulting in the best treatment. This research design used a completely randomized design (CRD) with the second treatment (80% wheat flour formulation + 20% Ambon banana peel flour). Based on effectiveness test calculations, the best treatment for Ambon banana peel egg rolls was found in F2, namely (80% wheat flour formulation and Ambon banana peel flour 20%). This can be seen from the results of calculating the yield value (NH), which has the highest value, namely 0.77. The best treatment is F2 which has a water content of 4.17%, fiber content of 2.97%, ash content of 2.53%, meanwhile, the organoleptic test gives average results of consumers stating a real level of liking with color hedonic test results of 4.40 % (like), aroma 4.47% (like), typical banana peel taste 4.60% (like), texture 4.13% (like) and overall acceptability (like).